Effects of the occurrence of a cyclone and the dominance of a bamboo species on the dynamics of subtropical forest fragments. (18th March 2019) - Liebsch, Dieter; de Maçaneiro, João Paulo; Galvão, Franklin; Marques, Marcia Cristina Mendes; Mikich, Sandra Bos
Abstract: With the intensification of global warming, the occurrence of large‐scale natural events is becoming even more common in tropical regions, which can impact the structure of plant communities. In this study, we evaluated the isolated and combined effects of an extratropical cyclone and the dominance of a native bamboo species ( Merostachys skvortzovii ) on floristic composition, diversity, demographic rates and the increment of trees in Atlantic Forest fragments in Southern Brazil. In 2014 (T1) and 2016 (T2), we sampled 56 plots of 200 m² for the effects of an extratropical cyclone in 2009 (T0). We also evaluated another 60 plots of the same size not in the direct path of this cyclone. Half of the plots in each group were covered by dense groupings of bamboos, as a result of past human activities, which could potentially limit natural regeneration. We observed an increase in richness and diversity indices ( H ′ and 1/ D ) from the first (T0) to the following assessments (T1 an T2) on the sites affected by the cyclone, when compared to non‐affected sites. After the cyclone, both density and basal area they decreased, but there was an increase in recruitment, mortality, turnover rates and basal area, as well as basal increment. The diameter increment on surviving individuals was higher in cyclone‐affected sites than in non‐affected sites. Bamboo cover did not affect richness or demographic rates (except mortality between T0 and T1). Natural impacts of this nature can lead to significant alterations of demographic rates, allowing the input of new species and influencing the pace of demographic processes.